KAJIAN MULTIDIMENSIONAL FAKTOR PENERAPAN GOOD RETAILING PRACTICES (GRP) PRODUK PANGAN SEGAR ASAL TUMBUHAN DI SUPERMARKET KOTA SURABAYA - Maratussholihah, Elvina Diah; Sentoso, Wahyu (Berkala Ilmiah AGRIDEVINA, 2019)
Modern retail is one of the links that significantly influences the sustainability of the food product supply chain from producers to end consumers. The purpose are evaluate the main components of the application of GRP in handling Fresh Food Plant Origin (PSAT) products at supermarkets in the city of Surabaya. Data analysis method with factor analysis approach (Factor Analysis) and supported by IBM SPSS Ver software. 23. The results of the analysis of the five components it is known that component 1 has the highest loading value on the 'Storage' factor of 0.829. The second component places the ‘Cleanup and Sanitation appropriate factor’ with a loading value of 0.928, while the third component is known as 'Waste Disposal' with a loading value of 0.913. The fourth and fifth components are each known as the 'Ingredient Inspection' and 'Food Handler Cleanliness' with loading values of 0.827 and 0.616 which must be carried out by modern retail management as a determinant of the success of the handling of Fresh Food from Plants (PSAT). DOI : https://doi.org/10.33005/adv.v8i2.1860